Singularities of the mechanism to protection of patron data library visitors in the legislation of EU and system of standards IFLA - Koval Tetiana; Lopata Olena (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2019)

(untitled)
The article highlights current issues of processing and protection of personal data in modern conditions, as well as analyses the problematic aspects of privacy in the practical activities of libraries. Modern issues of personal data, EU and IFLA data security safeguarding mechanism provided by law. The legislative nature of the term «personal data» according to European way of formation and determination of its law context are analyzed in the article. The history, chronology of development and mutual approval, as well as about the questions of application of Law of Ukraine «About the personal data protection» was reported. The main cause of this article is to study the legal norms of the European Union and the IFLA and ALA system of protection of personal data in modern conditions and compilation of legal requirements to establish an integrated system of protection of personal data in the library area. The case-method of this intelligence / work / chosen method of comparative analysis. The article analyzes the state of the Ukrainian legislation as related to restriction of the access to personal information, its compliance with the principles of international law in the European integration of Ukraine and examines the state of European law in this field. It is noted that, this broad topic definitely concerns librarians, as it is such a key part of the underpinnings of the profession. Non-regulated or weakly regulated by norms ISO aspects of the rules of data accounting and library statistics - ISO 2789:2013 standard «Information and documentation - International library statistics» and data security in the digital age - ISO / IEC 27001:2013 standard «Information Security Management Standards». Issues of quality of information, protection of personal data, and professional ethics in the library environment were discussed at the World Library and Information Congress (WLIC) in Lyon (August 16-22, 2014). The problem of regulatory regulation of relations in the library industry, including information security and personal data protection, was studied by the American Association of Law Libraries (hereinafter: AALL). In the Reports of Chapters, Special Interest Sections, Committees, Special Committees, Task Forces, and Council, Representatives, and Washington Affairs Office 2003-2004, the issue of information security in the library area/ is addressed in several key chapters. Throughout 2015 and 2016, The Intellectual Freedom Committee, part of the American Library Association (ALA), published a set of Library Privacy Guidelines that cover topics including K-12 student privacy, ebook lending and digital content privacy, library management system privacy, and public access computer privacy. As more systems that had historically been physically located in the library have moved toward service providers, a cross constituency activity was launched by NISO to create a set of principles for libraries, service providers, and publishers. The resulting framework includes key areas of focus such as transparency, the need for certain anonymous functionality, and explicit opt-in for data collection. In 2016, the Resource Access for the 21st Century (RA21) was launched to connect libraries, service providers, and publishers with the goal of helping ensure ease of access to scholarly content while protecting it from unauthorized access and distribution. The role of the V. I. Vernaskyi National Library of Ukraine in the implementation of European standards of data protection - organizational and technical, in the practice of library work was emphasized. In order for users to get the benefits they seek, librarians must make riskbased decisions on the value of the trade-off between security and/or privacy and the value of the service they seek to get from the library. The key is to give patrons, users, and the community the information and options to make smart, well-informed security and privacy decisions. Librarians can use their influence and skillsets to get their communities on a path to make patrons, whether inside or outside the library, wiser about their role in security and privacy and empowering them to insist on accountability from everyone around them regarding both areas of concern.